A Study of Bacterial Pathogens Associated with Diarrhea in HIV-Positive Patients (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
Diarrhea is a common complication of acquired immune deficiency syndrome (AIDS), occurring in almost 90% of AIDS patients in developing countries like Uzbekistan.